2003
DOI: 10.1892/0891-6640(2003)017<0791:eoeeno>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Enteral Nutrition on Intestinal Permeability, Intestinal Protein Loss, and Outcome in Dogs with Severe Parvoviral Enteritis

Abstract: A randomized, controlled clinical trial investigated the effect of early enteral nutrition (EN) on intestinal permeability, intestinal protein loss, and outcome in parvoviral enteritis. Dogs were randomized into 2 groups: 15 dogs received no food until vomiting had ceased for 12 hours (mean 50 hours after admission; NPO group), and 15 dogs received early EN by nasoesophageal tube from 12 hours after admission (EEN group). All other treatments were identical. Intestinal permeability was assessed by 6-hour urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…Puppies receiving early enteral nutrition via a nasoesophageal tube, compared to puppies that received nil per os until vomiting cease, show earlier clinical improvement, significant weight gain, as well as improved gut barrier function, which could limit bacterial or endotoxin translocation (Mohr et al 2003).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Puppies receiving early enteral nutrition via a nasoesophageal tube, compared to puppies that received nil per os until vomiting cease, show earlier clinical improvement, significant weight gain, as well as improved gut barrier function, which could limit bacterial or endotoxin translocation (Mohr et al 2003).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…However, early enteral nutritional support has been shown to be associated with more rapid clinical improvement (Mohr et al, 2003). Puppies fed via nasoesophageal feeding tubes from 12 hours after admission showed earlier improvement of clinical signs and had significant weight gain compared to puppies that were not fed until vomiting had stopped.…”
Section: Early Enteral Nutritionmentioning
confidence: 99%
“…Puppies fed via nasoesophageal feeding tubes from 12 hours after admission showed earlier improvement of clinical signs and had significant weight gain compared to puppies that were not fed until vomiting had stopped. Parameters reflecting improved intestinal barrier function were also observed, suggesting that early enteral nutrition may limit bacterial or endotoxin translocation from the intestines decreasing the potential resultant coliform septicaemia and SIRS (Mohr et al, 2003). Another study in puppies with haemorrhagic gastroenteritis showed that enteral nutrition could result in vomiting shortly after initiation of feeding, but this is probably not significant because tolerance to the food soon developed in these patients (Will et al, 2005).…”
Section: Early Enteral Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The concentration of canine α 1 -PI in feces (Fcα 1 -PI) has been shown to be clinically useful as a marker for GI protein loss in dogs ( Fig. 1), 13,14 and to be increased before the onset of clinical signs and/or hypoalbuminemia or panhypoproteinemia in Soft Coated Wheaten Terrier dogs with familial PLE (Vaden SL -PI/g feces. Observed-to-expected ratios for the serial dilution and spiking recovery of 9 and 6 fecal extracts ranged from 90.4 to 152.0% and from 71.3 to 112.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%